ANALISIS PENERAPAN E-GOVERNMENT MELALUI APLIKASI SISTEM FORMULIR ELEKTRONIK DAN INFORMASI (SI-FELI) OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) DI PROVINSI GORONTALO - Mohi, Widya Kurniati; Botutihe, Nuzlan; Karim, Marlin H. (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This study aimed to assess the implementation of e-government through the electronic form and information system application (Si-Feli) at the Public Works and Spatial Planning Office in Gorontalo Province. The research employed a descriptive analysis using a qualitative approach. The results indicated that the implementation of e-government through the Si-Feli application had not been optimally executed, both in terms of support, capacity, and value. This was attributed to the government’s insufficient efforts to socialize the application to the community, resulting in many citizens still visiting the UPTD for services. Other challenges faced in the implementation of e-government through the Si-Feli application included a lack of human resources for application management, inadequate technological infrastructure, and insufficient budget allocation for the development of the Si-Feli application.However, overall, both the government and the community have begun to perceive the benefits of implementing e-government through the Si-Feli application. Therefore, it is essential to enhance the socialization of the Si-Feli application and allocate budgets to facilitate its development.